MOTIF PERKAWINAN DIBAWAH UMUR di NAGARI ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (Studi kasus : Jorong Galagah) - Husna, Usrati - (Pendidikan Sosiologi, 2014)
Maturation age of marriage for both men and women aim to create ahappy home life, and avoid some of the negative effects such as divorce, financialproblems. Underage marriage in Alahan Panjang Nagari precisely in JorongGalagah in the last two years has increased, actors underage marriage with anaverage age of 14-20 years, they are no longer concerned with education. Thisstudy was conducted to determine what the motive underage marriage and whatimpact they felt after getting married, this study focused on women who performunderage marriages.Reality in this study were analyzed with the phenomenological theory ofAlfred Schutz. This study used a qualitative approach with descriptive type.Descriptive type is the type of research that guides researchers to explore socialsituations or photograph to be studied thoroughly, breadth and depth. Thetechnique of taking informants conducted by purposive sampling with as many as13 people with the informant informant criteria, ie actors underage marriages thatare focused on women, neighbors, parents, community leaders. Data used primarydata and secondary data. Data was collected by observation, interview anddocumentation. The unit of analysis is the individual with data analysis andhuberrman milles comprising the step of reduction, data presentation / analysis ofdata, drawing conclusions.The results of this study, namely the motive underage marriage: because ofthe motive, first avoiding promiscuity and pregnancy outside marriage, two lowawareness of the importance of education, Third reducing the economic burden ofthe family, four married against their will. In order to motive, matchmaking. Theimpact of under-age marriage, like divorce, causing economic hardship.